PEMANFAATAN MEDIA AUDIO VISUAL DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA KELAS IX DI SMP NEGERI 7 SINGARAJA - Darmika, I Ketut Agus Darmika; Sujana , I Putu Windu Mertha; Sidaryanti, Ni Nyoman Asri (Program Studi PPKn Universitas Pendidikan Ganesha, 2026)
The purpose of this study is to describe the use of audio-visual media in enhancing students’ learning motivation at SMP Negeri 7 Singaraja, to identify the obstacles or challenges encountered, and to formulate solutions to address those challenges. This study employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The data were analyzed qualitatively using the Miles and Huberman analysis technique, which includes data collection, data reduction, data display, and conclusion drawing. The results indicate that the use of audio-visual media has a positive impact on improving students’ learning motivation. Students appeared more focused, active, and enthusiastic when participating in lessons that utilized videos, animations, and interactive presentations. This media not only helps students understand the material more concretely but also creates a more engaging, interactive, and meaningful learning atmosphere. However, its implementation faces several challenges, such as limited facilities, technical constraints, and teachers’ pedagogical readiness, as well as diverse student characteristics. To overcome these challenges, adequate facilities, teacher training, participatory learning strategies, and alignment of media with clear instructional objectives are necessary to enhance the quality of both the learning process and outcomes.